2001
DOI: 10.1136/vr.149.15.452
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind evaluation of implants of gold wire at acupuncture points in the dog as a treatment for osteoarthritis induced by hip dysplasia

Abstract: Thirty-eight dogs with hip dysplasia were studied to evaluate the use of gold wire implants at acupuncture points around the hip joints. They were assigned at random into two groups of 19. In the treated group, gold wire was inserted through hypodermic needles at electrically found acupuncture points around both hips. In the control group, the areas were prepared in the same way but had only the skin pierced at sites which were not acupuncture points, with a needle of the same size as that used in the treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
27

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 9 publications
0
30
0
27
Order By: Relevance
“…The acupuncture-deviated treatment of different illnesses with gold implants, in particular rheumatism-caused pain from the involved joint, has apart from a minor study by Hielm-Bjorkman et al (2001) on dogs to my knowledge not resulted in scientific publications until now. However, if the rationale behind the authorised treatment with chemically bound gold ions, for example GSTM and auronofin, performed at many hospitals around the world holds true (Vernon-Roberts 1979;Fleming et al 1996;Hostynek 1997), gold implants and gold-containing drugs 451 Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The acupuncture-deviated treatment of different illnesses with gold implants, in particular rheumatism-caused pain from the involved joint, has apart from a minor study by Hielm-Bjorkman et al (2001) on dogs to my knowledge not resulted in scientific publications until now. However, if the rationale behind the authorised treatment with chemically bound gold ions, for example GSTM and auronofin, performed at many hospitals around the world holds true (Vernon-Roberts 1979;Fleming et al 1996;Hostynek 1997), gold implants and gold-containing drugs 451 Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In the early 1970s some US veterinarians started to treat dogs suffering from hip dysplasia with gold implants, and since then several veterinary surgeons and medical doctors have implemented the technique on their patients (Hielm-Bjorkman et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Six unrelated dogs received for routine postmortem examination at the Department of Basic Sciences and Aquatic Medicine, Norwegian School of Veterinary Science, were included as controls for the current study (dog Nos. [10][11][12][13][14][15]. Three control dogs (dog Nos.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…This technique is derived from acupuncture and has been used in veterinary medicine for the past decade, largely as a treatment in canine hip dysplasia. 10 A recent double-blind, placebocontrolled clinical trial performed by Jaeger et al showed that the performance of dogs with hip joint osteoarthritis significantly improved after receiving gold bead implants. 13 Although it is widely accepted that gold may have an anti-inflammatory effect, it may cause hypersensitivity and tissue inflammation.…”
mentioning
confidence: 99%
“…Previous clinical studies support the long-term effects of gold implantation, although it is still controversial [5,[7][8][9][10]. Jaeger et al [10] reported that the pain-relieving effect of gold bead implantation in dogs with hip dysplasia continued throughout the 2-year follow-up period.…”
Section: Introductionmentioning
confidence: 96%